Prevalence of Musculoskeletal Disorders Among Low to High Mileage Non-Occupational Car Drivers in City Faisalabad: Musculoskeletal Disorders Among Low to High Mileage Non-Occupational Car Drivers - Ahmad, Jawad; Khalid, Amna; Aamir, Aatiqa; Zia, Huma; Younis, Khadija (Pakistan Journal of Health Sciences, 2020)
Musculoskeletal discomfort has been reported among the non-occupational car drivers covering low to high mileage to reach their jobs or other destinations. Domestic driving, driving to reach the job, social driving, and driving for leisure activities is also found to cause discomfort among people. This can affect their daily life activities and socioeconomic status. Objective: The purpose for which this study was conducted was to find out the musculoskeletal problems that could possibly arise among the common population of car drivers and among them the problem with highest ratio, due to various contributing risk factors. Methods: A cross-sectional study was carried out in city Faisalabad among non-occupational drivers in which 192 drivers including both males and females were enrolled with age limit from 18 to 60 years. Nordic musculoskeletal questionnaire was used to evaluate the pain in various areas of body in non-occupational drivers. Results: The results showed that the highest affected area was backache. There was 41% small back pain in last twelve months and 38% in last seven days among non-occupational car drivers. Conclusion: Low back pain was highest to be discovered in the time period of last 12 months and also in the last week as compared to other areas of body.